Impact of Urinary Incontinence on Quality of Life among Residents Living in Turkey - Guzelsoy, Muhammet; Demirci, Hakan; Coban, Soner; Belkiz Güngör, Buket; Ustunyurt, Emin; Isildak, Serhat (Urology Journal, 2014)
Abstract Purpose:To assess the impact of urinary incontinence on the quality of life in Turkish population. Materials and Methods: This was a cross-sectional study performed on 530 participants admitted to Sevket Yilmaz Research Hospital in Turkey. Quality of life (QoL) was assessed using Incontinence Impact Questionnaire (IIQ-7). Frequency and severity of urinary incontinence (UI) were diagnosed by answers to the International Consultation on Incontinence Questionnaire Short Form (ICIQ-SF) instrument. The relationship between several demographic data and QoL was examined. Results: The mean age of the attendees was 55.36 ± 10.62 years (range 40-91). A total of 109 (44%) women and 46 (16%) men suffered involuntary urine leakage. QoL changes for all domains showed significant deteriorations. Frequency and severity of UI were negatively associated with the QoL scores. Conclusion: Our results have shown that, UI considerably worsens QoL. Challenge with UI should be priority of any project aiming to promote the quality of life.